PERKEMBANGAN INDUSTRI GULA INDONESIA DAN URGENSI SWASEMBADA GULA NASIONAL - Yanto Togi Ferdinand Marpaung; Parulian Hutagaol; WH Limbong; Nunung Kusnadi (Indonesian Journal of Agricultural Economics, 2011)
Indonesia Sugar Indonesia experiences declining trend since year early 1930 until thisrecent years. It describes by the low of productivity level such as sugar yield, rendemen andthe increasing demand of sugar import. Facing those facts, therefore it is important to studythe development of of sugar industry in Indonesia and the importance of achieving sugarself sufficiency program. In order that, this articles show the big picture of Indonesia sugarindustry and how they interrelated with the sugar self-sufficiency program.Keywords: sugar, self-sufficiency program, sugar development